DISCOVERY AND RESEARCH OF THE MUSLIM CULTURAL COMPLEX OF THE X - EARLY XIII CENTURY IN DERBENT (preliminary report) - Gadziev, M S; Abiev, A K; Budajciev, A L; Abdullaev, A M; Sausev, K B (History, Archeology and Ethnography of the Caucasus, 2015)
The short review of archaeological researches of the new revealed object of cultural heritage in Derbent is presented in the article. The monumental Muslim cult complex connected with system of water supply was revealed as a result of the carried-out works. This complex included the stone steles with Muslim religious texts in the Arabic language, a platform of cult building, stone and ceramic tubes water conduits, water-collecting sumps, large basins. Paleographic features of the inscriptions, numerous finds of coins and the accompanying archaeological material (first of all, pottery) define a time of active functioning of the complex during the 10-th – the beginning of the 13-th century AD.
Keywords: Derbent; Bab al-abwab; Islam; Cult site; Epigraphics; water supply